2015
DOI: 10.1111/2041-210x.12347
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical expectations of the Isolation–Migration model of population evolution for inferring demographic parameters

Abstract: Summary1. The Bayesian inference of demographic parameters under an Isolation-Migration (IM) model of population evolution offers a major improvement over previously available approaches. This method is implemented in a popular program, IMa, widely used in population genetic studies. 2. While the robustness of the method to deviations of the IM model has previously been evaluated, we assess the performance of the program with two populations when the model used to generate the analysed data meets the assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Violations of these assumptions have been shown to bias estimates of gene flow (Becquet & Przeworski, ; Strasburg & Rieseberg, ). False‐positive rates were found when testing for the presence of migration using likelihood ratio tests in small data set (~5–50 loci of 2,500 bp) and low divergence time (Cruickshank & Hahn, ) or small number of sample sites (Quinzin, Mayer, Elvinger, & Mardulyn, ). Two other important limitations of IM model are the assumption of a constant effective deme size and the inability to fit more complex and realistic models, including those with secondary contacts.…”
Section: How To Quantify Non‐effective and Effective Dispersal Rates mentioning
confidence: 99%
“…Violations of these assumptions have been shown to bias estimates of gene flow (Becquet & Przeworski, ; Strasburg & Rieseberg, ). False‐positive rates were found when testing for the presence of migration using likelihood ratio tests in small data set (~5–50 loci of 2,500 bp) and low divergence time (Cruickshank & Hahn, ) or small number of sample sites (Quinzin, Mayer, Elvinger, & Mardulyn, ). Two other important limitations of IM model are the assumption of a constant effective deme size and the inability to fit more complex and realistic models, including those with secondary contacts.…”
Section: How To Quantify Non‐effective and Effective Dispersal Rates mentioning
confidence: 99%
“… Strasburg and Rieseberg (2010) highlighted that assumption misspecification can lead the program IM ( Hey 2010 ) to deliver biased answers. Recently, Quinzin et al (2015) evaluated the program IM and observed that divergence time estimates are more accurate if migration is low and if the populations are large compared to the divergence time. We find similar patterns with Migrate and IMa2p .…”
Section: Discussionmentioning
confidence: 99%
“…Because either model is not flawless, we integrated the divergence time calculated by the 2 models. In the IM model, the divergence time is best estimated in the scenario of gene flow equals to zero ( Quinzin et al 2015 ), and in the gene flow case the coalescent time of the samples predate the divergence time ( Wilkinson-Herbots 2008 ), so we put the divergence time estimated by IM as the right boundary. The “complete isolation” model does not consider gene flow, the divergence time estimated by *Beast may posterior to the divergence time ( Wilkinson-Herbots 2008 ), so we put it as the left boundary.…”
Section: Discussionmentioning
confidence: 99%